FAKTOR-FAKTOR YANG BERHUBUNGAN TERHADAP KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) - Rahmidha Dwijayanti; Setiawan .; Darjati . (Poltekkes Kemenkes Surabaya, 2019)
Sanitation of public locations is a rather urgent health issue because public places are the meeting paces of people with various diseases, similar to local government clinic. This study was aimed to analyze attitudes on ARI incidences in Wiyung Local Government Clinic of Surabaya.This study was an observational analytic study with case control approach. Population and sample of the study were suferer’s in Wiyung Local Government Clinic of Surabaya, with total sample 38 suferer’s and 38 control. Analysis using statistical test, the test used is the chi square test.Based on chi square test for environmental factors, there are results that ventilation, lighting intensity, temperature, humidity, and density bedroom are relate with Acute Respiratory Infections (ARI) event because p is less than α (0,05). While for behavioral factors there are results that knowledge, attitude, and practice are relate with Acute Respiratory Infections (ARI) event because p is less than α (0,05).Suggestion sufferer Acute Respiratory Infections (ARI) constant keep environmental sanitation room, with keep sanitation outside room please escaped from contaminate disease, while to Local Government Clinic please optimize character personnel environmental health as educator inside give information about environmental factors and behavioral factors about event Acute Respiratory Infections (ARI). Keywords: Acute Respiratory Infections, environmental factors